Dyadic Coping in Aging: Linking Self-Perceptions of Aging to Depression - Jose Adrián Fernandes-Pires; Guy Bodenmann; María Márquez-González; María del Sequeros Pedroso-Chaparro; Isabel Cabrera; Laura García-García; Andrés Losada-Baltar (Geriatrics)
Negative self-perceptions of aging have been linked to poorer health and quality of life and predict significantly depressive symptomatology. The support provided by the partner may have an impact on the effects of self-perceptions of aging on depressive symptoms; a close relationship can go along with additional stress or resources and benefits. The present study analyzes the relationship between negative self-stereotypes and depressive symptomatology, considering positive and negative dyadic coping (DC) as moderator variables in this association. Method: Participants were 365 individuals (convenience sample) 40 years or older (M = 60.86) involved in a partner relationship. Participants completed a questionnaire that included the following variables: negative self-perceptions of aging, positive DC (e.g., “My partner shows empathy and understanding to me”), negative DC (e.g., “When I am stressed, my partner tends to withdraw”), and depressive symptomatology. Two moderation models were tested by linear regression. Results: The effect of negative self-perceptions of aging on depressive symptoms was moderated by positive and negative DC only in women. The effect of negative self-perceptions of aging appears to be smaller among those women with higher levels of positive DC and lower levels of negative DC. Conclusions: Positive DC might buffer the association between negative self-perceptions of aging and depressive symptoms. Negative DC might amplify this association, as it is associated with lower well-being among women who express negative self-perceptions of aging. Implications: Training couples in strategies for providing supportive dyadic coping may be a resource to buffer the negative effect of negative self-perceptions of aging on well-being.